The recoverability of romantic gifts: Kua Tee Beng v Ye Caiyan [2015] SGHC 53 - SEE, Alvin W. L. (Institutional Knowledge at Singapore Management University, 2015)
This case concerned an attempt by a man to recover from his former lover payments and gifts made to her while they were in a romantic relationship. Notwithstanding that the main battle was chiefly fought within the realm of evidence, the case raised interesting legal issues of property law that merit closer attention.